Hydrology influences carbon flux through metabolic pathways in the hypolimnion of a Mediterranean reservoir - Montes-Pérez, Jorge Juan; Marcé Romero, Rafael; Obrador Sala, Biel; Conejo-Orosa, Teresa; Díez, J. L.; Escot, Carmelo; Reyes, I.; Moreno-Ostos, Enrique (Springer, 2022)
Global change is modifying meteorological and hydrological factors that influence the thermal regime of water bodies. These modifications can lead to longer stratification periods with enlarged hypolimnetic anoxic periods, which can promote heterotrophic anaerobic processes and alter reservoir carbon cycling. Here, we quantified aerobic and anaerobic heterotrophic processes (aerobic respiration, denitrification, iron and manganese reduction, sulfate reduction, and methanogenesis) on dissolved inorganic carbon (DIC) production in the hypolimnion of a Mediterranean reservoir (El Gergal, Spain) under two contrasting hydrological conditions: a wet year with heavy direct rainfall and frequent water inputs from upstream reservoirs, and a dry year with scarce rainfall and negligible water inputs. During the wet year, water inputs and rainfall induced low water column thermal stability and earlier turnover. By contrast, thermal stratification was longer and more stable during the dry year. During wet conditions, we observed lower DIC accumulation in the hypolimnion, mainly due to weaker sulfate reduction and methanogenesis. By contrast, longer stratification during the dry year promoted higher hypolimnetic DIC accumulation, resulting from enhanced methanogenesis and sulfate reduction, thus increasing methane emissions and impairing reservoir water quality. Aerobic respiration, denitrification and metal reduction produced a similar amount of DIC in the hypolimnion during the two studied years. All in all, biological and geochemical (calcite dissolution) processes explained most of hypolimnetic DIC accumulation during stratification regardless of the hydrological conditions, but there is still ~ 30% of hypolimnetic DIC production that cannot be explained by the processes contemplated in this study and the assumptions made.
Keywords: Anoxia; Thermal stratifcation length; Hypolimnion; Dissolved inorganic carbon; Metabolic rate; Sulfate reduction; Methanogenesis; Anoxia